Awareness and Knowledge Levels of Osteoporosis in Patients with Multiple Sclerosis - Ali Karakaş; Nihan Erdinç Gündüz; Sinem Özçelik; Hatice Limoncu; Banu Dilek; Selmin Gülbahar; Serkan Özakbas; Minuse Özlen Peker (Galenos Yayinevi, 2022)
Objective:This study examines the awareness and knowledge levels of osteoporosis in patients with multiple sclerosis (MS).Materials and Methods:A total of 88 adult patients with MS (22 male, 66 female) were included in the study. The demographic and socioeconomic status of all patients were recorded. First, a question was asked the participants: "Have you ever heard of osteoporosis before?". After that, a survey was conducted on the participants. The survey consisted of a questionnaire assessing their knowledge using a 30-item instrument reflecting 9 knowledge domains (eg, risk factors, diagnosis, prognosis).Results:The mean age of the patients was 39.85±9.67 years. The duration of the disease was median [interquartile range (IQR) (Q1-Q3) 4 (1-10)] years. Expanded disability status scale score of the patients was median [IQR (Q1-Q3) 2 (1-4.5)]. Most of the participants (81.8%) were aware of osteoporosis. Awareness of osteoporosis was higher in those who received corticosteroid treatment and had comorbid diseases (respectively p=0.011 and p=0.009). On average, the knowledge questions score was 13 (0-23). Mean knowledge scores were not associated with education status or gender. The knowledge score levels were higher in those who had heard of osteoporosis than in those who had not heard, respectively 14 (10-18) to 4 (0-13,75) (p<0.001).Conclusion:Although awareness of osteoporosis was high in MS patients, the level of knowledge on osteoporosis was insufficient. Awareness and knowledge levels of osteoporosis were higher in those who received corticosteroid treatment. Additionally, osteoporosis awareness was higher in those who had comorbid diseases. Increasing knowledge about osteoporosis may be important for preventing osteoporosis and reducing its complications in MS patients.